(untitled) (Fiep Bulletin - online, 2011)
The study of what is being a researcher is necessary when we see the classes in the school guided by common sense, "in I think something is so, and thus we see how our education is poor, producing students who can not make sense and meaning to their learning. From this fact, the analysis of physical education classes, we can see that the specificities of this field is not present, but for the purpose of helping others school disciplines, the teachers can not see the construction of knowledge of their students to participate this process. Thus, we see that assigning the role of the teacher researcher is important for improving education, we will not be producing new science, but reframe the same, providing an education to students, and somehow society, foundations today are concentrated only in academic field. However, for this change there is no other way except by their own teacher formation, either in their initial formation or continued. If the objective of this research, promote reflection together with other teachers of the need for continued study, openness to new knowledge, a break with the paradigms that no longer serve the needs of our current society, and that the relationship of teacher researcher is possible, including different dimensions, the theory curriculum, teacher formation, public politics, the educational paradigms, theories of teaching, learning theories, didactics, the especifics knowledges. And with this set of knowledge the teacher researcher will know to give your student a quality education.